Organizational evolution and the Olympic Games: the case of sport climbing - Batuev, M.; Robinson, L. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
This paper discusses the processes underpinning the evolutionary development of sport climbing in recent decades, with a particular focus on the impact of its inclusion in the Olympic Games. New institutionalism and resource-dependence theory provide an analytical and explanatory framework for this study. The research adopted a qualitative method strategy comprising a series of interviews and the analysis of documents, reports, press and social media. The recent inclusion of the sport in the Tokyo 2020 Olympic programme has created challenges, primarily because of strong values inherent within the sport. The research, however, shows that the values of a sport can expand and develop in order to fit the regulatory legitimacy required by inclusion in the Olympic Games. Nonetheless, the research also shows that involvement with the IOC raises questions about who `owns` the sport.